KAJIAN KUAT LENTUR BETON FS’45 DENGAN BAHAN TAMBAH GEOGRID - Prawijaya, Muhammad Tarish; Rosyad, Farlin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Building construction found in Indonesia generally uses concrete as its main structural material, the need for concrete in construction is very large. This is because concrete has many advantages when compared to other building materials. Especially concrete that has high compressive strength. According to the general specifications of Bina Marga (2018) revision 2, Concrete is a mixture of Portland cement or equivalent hydraulic cement, fine aggregate, coarse aggregate, and water with or without additives to form a solid mass. Concrete is also widely used in building construction because it has advantages including being easy to form according to plan, raw materials or concrete components are easy to obtain, durable, fire resistant, easy and relatively cheap maintenance costs and concrete is a structure that has high compressive strength. So researchers are interested in conducting research using geogrids to analyze the effect of geogrids as additives in concrete mixtures. And because the weakness of concrete is its low ability to withstand flexural strength, in this study the researcher will analyze the effect of geogrid as an additional material for fs'45 concrete on the flexural strength of fs'45 concrete and analyze the comparison of normal fs'45 concrete with FS 45 concrete with geogrid additional material.Keywords: Geogrid added concrete